The method validation of formaldehyde quantitation in textile - Promrangsan, Nart (Bulletin of Applied Sciences, 2022)
The determination of formaldehyde in textile by high performance liquid chromatographic technique (HPLC) with diode array detection. The sample was prepared using the standard methods: ISO 14184-1 and ST 2002. Formaldehyde was extracted with water at 40 °C then reacted with 2,4-dinitrophenylhydrazine to form complex compound, which has an absorption at 360 nm. The complex was quantitatively determined using HPLC with diode array detector at 360 nm. Limit of detection (LOD) and limit of quantitation (LOQ) were 0.66 and 7.6 mg/kg, respectively. The method gave linear range at 7.6 to 86.8 mg/kg, which can be accurately used to determine formaldehyde in textile in direct contact with skin. According to European standard, textile used for children must contain formaldehyde less than 30 mg/kg, and in Japan, for infant (<24 month old) it must be less than 16 ug/g and for children over 24 month old must not be more than 75 ug/g. The validation of the method was studied using parameters such as linearity, limit of detection, limit of quantitation, bias, precision, matrix effect and estimation of uncertainty. The recovery was between 90 and 110%. The precision, expressed as relative standard deviation (%RSD), was less than 5 %. The matrix effect was evaluated by the recovery and it was found that this method was not affected by matrix. Both bias and precision were used to obtain estimation of measurements uncertainty. The expanded uncertainty was not exceeding 20 % with a confidence level of 95 % which was acceptable for the uncertainty target. Thus the developed and validated method was suitable to be used for quantitative determination of formaldehyde in textile using high performance liquid chromatography.